Two Isophalerin Compounds from Ethyl Acetate of Leave and Fruit of Mahkota Dewa (Phaleria macrocarpa (Scheff.) Boerl.) and Its Antibacterial Activity - Susilawati Susilawati; Sabirin Matsjeh; Harno Dwi Pranowo; Chairil Anwar (Universitas Gadjah Mada, 2015)
Mahkota dewa plant (Phaleria macrocarpa (Scheff.) Boerl.) which is belong to family of Thymelaeaceae is one of Indonesia's traditional medicines. The aim of this research is to isolate secondary metabolites from ethyl acetate extract of leave and fruit of mahkota dewa and to determine the molecular structure of isolated compounds using spectroscopic method and to know the antibacterial activity of the isolated compound. Sample was extracted with methanol, concentrated then extracted by n-hexane, chloroform and ethyl acetate. The compounds were separated and purified with column chromatography. The compound 1 was isolated from ethyl acetate extract of leave as white needle amorphous solid as 45 mg. The compound was identified by spectroscopic as 4,6-dihydroxy-4’-methoxybenzophenon-2-O-β-D-glucopyranoside and named isophalerin B. From the test results of antibacterial activity showed that the compound 1 (10 mg/mL) in ethanol has a weak activity against the bacteria S. aureus and E. coli. The compound 2 was isolated from ethyl acetate extract of fruit as peach needle crystal as 10 mg. The compound was identified by spectroscopic as 4,6-dihydroxy-4’-methoxybenzophenon-2-O-α-D-glucopyranoside and named isophalerin A.